2022
DOI: 10.3390/ijms23010575
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Targeted Cancer Therapy Approach Mediated by RNA trans-Splicing In Vitro and in a Xenograft Model for Epidermolysis Bullosa-Associated Skin Cancer

Abstract: Conventional anti-cancer therapies based on chemo- and/or radiotherapy represent highly effective means to kill cancer cells but lack tumor specificity and, therefore, result in a wide range of iatrogenic effects. A promising approach to overcome this obstacle is spliceosome-mediated RNA trans-splicing (SMaRT), which can be leveraged to target tumor cells while leaving normal cells unharmed. Notably, a previously established RNA trans-splicing molecule (RTM44) showed efficacy and specificity in exchanging the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…High-risk patients may be more sensitive to chemotherapy of these drugs. A previous study reported that spliceosome-mediated RNA trans-splicing (SMaRT) could effectively overcome the obstacle that chemotherapy could not clear cancer cells with tumor specificity ( Woess et al, 2022 ). Their study could explain that the different chemoresistance between groups may be related to alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk patients may be more sensitive to chemotherapy of these drugs. A previous study reported that spliceosome-mediated RNA trans-splicing (SMaRT) could effectively overcome the obstacle that chemotherapy could not clear cancer cells with tumor specificity ( Woess et al, 2022 ). Their study could explain that the different chemoresistance between groups may be related to alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several laboratories work extensively for the establishment of both primary and metastatic cSCC cell lines ( 83 , 84 ). Furthermore, the use of the skin derived SCC cells assumes a significant meaning also in the context of those SCCs arising from a genetic condition, such as the RDEB (recessive dystrophic epidermolysis bullosa) where a targeted therapy approach is required ( 85 ).…”
Section: In Vitro Modelsmentioning
confidence: 99%